(untitled) (Journal of Pathology of Nepal, 2025)
Background: Cervical cancer ranks as the fourth most common cancer in women worldwide. Accurate histologic interpretation of cervical intraepithelial neoplasia (CIN) is often challenging due to significant interobserver variability. Immunomarkers such as p16/INK4a and Ki-67 have emerged as valuable tools in detecting high-risk HPV-associated dysplasia, and minimizing diagnostics inconsistencies. Materials and Methods: A prospective cross-sectional study was carried out between June 16, 2019, to June 14, 2020, at Department of Pathology, Tribhuvan University Teaching Hospital, Nepal. Of 117 cervical biopsies received, 111 of these were included in the study. p16 and Ki-67 immunostaining were done on 71 cases with suspected intraepithelial lesion or malignancy. Results: Among 111 cases, chronic cervicitis was most common [58 (52.70%)], followed by premalignant lesions [33 (30.63%)] and invasive carcinoma [20 (17.11%)]. None of the cases of chronic cervicitis expressed p16, while 24 (73%) premalignant lesions and 17 (94.73%) invasive carcinomas were positive . Ki-67 score was 0 in 15 (83.30%) cases of chronic cervicitis but premalignant lesions and invasive carcinomas showed increasing positivity (scores 1-3). A significant correlation was observed between Ki-67 score and cervical neoplasia grade (p-value < 0.001). Concordance between H&E diagnosis and final diagnosis after IHC was 88% (κ = 0.853, P < 0.05). Conclusions: p16 and Ki-67 can be used as complementary, surrogate markers for HPV related cervical neoplasia and help in confirming the histologic diagnosis. These immunostains aid in accurate diagnosis of cervical intraepithelial lesions by reducing interobserver variability and aid in the distinction between reactive and neoplastic changes.